Resource implications of the latent tuberculosis cascade of care: a time and motion study in five countries - H. Alsdurf; O. Oxlade; M. Adjobimey; F. Ahmad Khan; M. Bastos; N. Bedingfield; A. Benedetti; D. Boafo; T. N. Buu; L. Chiang; V. Cook; D. Fisher; et al. (BMC, 2020)
Abstract Background The End TB Strategy calls for global scale-up of preventive treatment for latent tuberculosis infection (LTBI), but little information is available about the associated human resource requirements. Our study aimed to quantify the healthcare worker (HCW) time needed to perform the tasks associated with each step along the LTBI cascade of care for household contacts of TB patients. Methods We conducted a time and motion (TAM) study between January 2018 and March 2019, in which consenting HCWs were observed throughout a typical workday. The precise time spent was recorded in pre-specified categories of work activities for each step along the cascade. A linear mixed model was fit to estimate the time at each step. Results A total of 173 HCWs in Benin, Canada, Ghana, Indonesia, and Vietnam participated. The greatest amount of time was spent for the medical evaluation (median: 11 min; IQR: 6-16), while the least time was spent on reading a tuberculin skin test (TST) (median: 4 min; IQR: 2-9). The greatest variability was seen in the time spent for each medical evaluation, while TST placement and reading showed the least variability. The total time required to complete all steps along the LTBI cascade, from identification of household contacts (HHC) through to treatment initiation ranged from 1.8 h per index TB patient in Vietnam to 5.2 h in Ghana. Conclusions Our findings suggest that the time requirements are very modest to perform each step in the latent TB cascade of care, but to achieve full identification and management of all household contacts will require additional human resources in many settings.